2004
DOI: 10.1111/j.1440-1843.2004.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effectiveness of an inpatient pulmonary rehabilitation program for elderly COPD patients: Comparison between young‐elderly and old‐elderly groups

Abstract: Pulmonary rehabilitation is an effective treatment in terms of improving dyspnoea, exercise capacity and HRQoL in elderly COPD patients, and the benefits are almost comparable for young-elderly and old-elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 41 publications
2
24
0
8
Order By: Relevance
“…For example, 1 study compared the effects of a 2-week inpatient rehabilitation program between patients 65 to 74 years and patients >75 years and found similar improvements in exercise capacity, dyspnea, or healthrelated quality of life. 51 Another study showed that although inpatient pulmonary rehabilitation was associated with greater improvements in walk distance in patients <60 years of age, pulmonary rehabilitation was well tolerated in older adults and resulted in significant improvements in functional capacity among elderly patients (including patients >80 years of age). 52 Finally, outpatient pulmonary rehabilitation has also been associated with significant improvements in walk distance and lung function irrespective of age.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 98%
“…For example, 1 study compared the effects of a 2-week inpatient rehabilitation program between patients 65 to 74 years and patients >75 years and found similar improvements in exercise capacity, dyspnea, or healthrelated quality of life. 51 Another study showed that although inpatient pulmonary rehabilitation was associated with greater improvements in walk distance in patients <60 years of age, pulmonary rehabilitation was well tolerated in older adults and resulted in significant improvements in functional capacity among elderly patients (including patients >80 years of age). 52 Finally, outpatient pulmonary rehabilitation has also been associated with significant improvements in walk distance and lung function irrespective of age.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 98%
“…The benefits probably relate to a degree of deconditioning in the older adult group and benefits in terms of exercise capacity do begin to diminish at 12 months in this group. 19 Although the recent NICE COPD guidelines emphasised the importance of pulmonar y rehabilitation, access to services is by no mean universal in the UK at present.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
“…Education and self-management intervention has been shown to reduce unplanned dependence on healthcare professionals and an overall reduction in cost [7]. Overall, the PR programs generate end results equivalent to usual care, but programs containing > or = 3 components show lower relative risks for hospitalization and healthcare resource utilization [8][9][10] in both young and elderly patients [11]. In a cost utility study based on a 6-week program, each rehabilitation program for up to 20 patients cost 12,120 GBP.…”
Section: Introductionmentioning
confidence: 99%